STIMULANT USAGE BY MEDICAL STUDENTS FOR COGNITIVE ENHANCEMENT: A SYSTEMATIC REVIEW - Plumber, Noorine; Majeed, Maliha; Ziff, Shawn; Thomas, Sneha E.; Bolla, Srinivasa Rao; Gorantla, Vasavi Rakesh (CUREUS INC, 2021)
Stimulants have been used throughout human history for a variety of reasons. High levels of stress and the demanding nature of medical school make their usage among medical students particularly common. The most prevalent stimulant used by students is coffee, followed by tea and other forms of caffeine like sugary energy drinks. In addition, amphetamine-based medications for treating attention deficit hyperactivity disorder (ADHD) have been increasing in popularity, which many students take illicitly. Students report taking various forms of stimulants to promote cognitive enhancement, prolong wakefulness and retain focus for long periods of time. Moderate doses of caffeine and amphetamines would lead to enhanced alertness and concentration. However, large increases in dosage or frequency would lead to an increased risk of toxicity and adverse effects. The positive outcomes from stimulant consumption are often overshadowed by the negative side effects and incorrect dosage. Thus, it appears that usage of stimulants should be limited, in favor of a more sustainable approach to cognitive enhancement. This review analyzes the use of stimulants among the medical student community, consequences of misuse and discussed the healthy and organic approaches to lessen the stress and improve academic performance. This article also discusses the mechanisms of action, acceptable doses, additives, ingredients of stimulants commonly used by medical students for cognitive enhancement and the implications of long-term use as the stress of practicing medicine extends well beyond the medical school years.
Keywords: energy drink; smart pills; stimulant; cognitive enhancer; amphetamine; caffeine; Type of access: Open Access